Blue Carbon Policy Direction in Optimizing the Potential of Coastal Areas - Mulya, Josua; Naiborhu, Netty; Rini, Nicken; Vico, Nanda (Magister of Law, Faculty of Law, University of Mataram, 2025)
The potential of coastal areas through coastal and marine ecosystems is very important to minimize the increase in carbon emissions by becoming a means of carbon absorption through the blue carbon mechanism. Blue carbon has the potential because of its role in carbon sequestration to minimize the impact of the climate crisis. Unfortunately, the potential of blue carbon through coastal areas is not in line with policies that do not manifest optimal environmental optimization. To maximize the potential of blue carbon and protect coastal ecosystems, it is necessary to reorient derivative policies and revoke policies that have the potential to threaten coastal ecosystem areas. The method used in this study is normative juridical, with a policy approach and a conceptual approach. This research is based on the hypothesis that the central government demonstrates insufficient resolve about determining and implementing efforts to optimize coastal areas, with an economic orientation that emphasizes coastal ecosystems leading to policy directions towards exploitation rather than conservation. Thus, the direction of the blue carbon policy is expected to be synchronous and optimal to explore the potential of Indonesia’s coastal areas and contribute to significantly reducing the impact of the climate crisis.